“Hallelujah”, “Iye”, “Hosannah”: Investigating the Conversational Dynamics in Prayers of the ESOCS Church - Amadi, Gabriel Ndamzi (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study utilizes Conversational Analysis (CA) theory to examine the discourse and conversational dynamics in the prayers of the Eternal Sacred Order of the Cherubim and Seraphim (ESOCS) Church, a spiritually vibrant community known for its fervent, linguistically rich prayers. ESOCS prayers are rooted in distinctive traditions that incorporate scriptural references, ritualistic expressions, and emotional outpourings, offering a rich domain for linguistic analysis. The study analyzes 4 prayer samples, selected from an initial pool of 45 prayer recordings collected across 22 ESOCS church branches worldwide, focusing on dialogicity, foregrounding, cohesion, adjacency pairs, and prosody. The findings reveal that an interactive exchange between linguistic structure, cultural practices, and spirituality characterizes ESOCS prayer dialogue. Dialogicity, rhetorical strategies, and prosody play a significant role in fostering the congregation's active engagement, unity, and reverence. Furthermore, cohesion techniques and the use of adjacency pairs reflect the cultural values that shape the prayer experience, enhancing both clarity and emotional depth. This investigation offers insights into the unique conversational dynamics of ESOCS prayers and contributes significantly to the growing literature on religious discourse analysis, particularly, in the context of prayers.